A simple dilution method for the direct determination of trace nickel in crude oil with a miniaturized electrothermal atomic absorption spectrometer. Issue 11 (23rd September 2020) - Li, Kai; Wu, Xi; Chen, Zhiming; Luo, Jin; Hou, Xiandeng; Jiang, Xiaoming
Abstract : A simple procedure for the direct determination of trace nickel in crude oil samples has been proposed using a miniaturized electrothermal atomic absorption spectrometer (ETAAS). Abstract : A simple procedure for the direct determination of trace nickel in crude oil samples has been proposed using a miniaturized electrothermal atomic absorption spectrometer (ETAAS). Prior to the analysis, crude oil in cyclohexane without any complicated or lengthy sample digestion was employed to suit a potential field analysis. A proper aliquot of the oil-based standard stock solution of Ni or crude oil was diluted in 20 mL cyclohexane, followed by 30 min ultrasonication and 60 min shaking. A tiny aliquot (20 μL) of the diluted sample solution was directly pipetted onto a tungsten coil (W-coil) atomizer of the miniaturized ETAAS (Fig. S1). With the heating program of the W-coil, the sample solvent and matrix were first removed, and the nickel was subsequently atomized for the AAS detection using palladium as a chemical modifier. Under optimized drying conditions, ashing and atomization currents, gas flow rate and atomizer height, a limit of detection (LOD) of 10 μg kg −1 was achieved, which satisfies the demands of field analysis for petroleum exploration. The accuracy of the proposed method for the determination of Ni in real crude oil samples was assessed by comparing the analytical data with those obtained via ICP-OES after microwave digestion, and the reproducibility was also investigated by analyzing 50 crude oil samples. The statistical results indicated that this is potentially useful for the field analysis of Ni in crude oil.